Using Flipped Classroom Approach to Teach Adjectives for Malaysian Year 4 Chinese ESL Learners - Teo Woon Chun; Ramesh Sathappan (The English Teacher, 2020)
This study was aimed at investigating the effectiveness of using Flipped Classroom Approach to teach adjectives to Malaysian Year 4 Chinese ESL learners. It was also designed to examine Malaysian Year 4 Chinese ESL learners’ perceptions towards Flipped Classroom Approach. Two classes with 10 Year 4 Chinese ESL learners in Sekolah Jenis Kebangsaan X were chosen as the research samples to form the experimental and control groups of this study. This intervention focused on the experimental group using Edmodo to acquire input before the lesson, while the control group followed the traditional classroom approach. This quasi- experimental research used several instruments to collect the data namely pre- and post- tests as well as questionnaires. The results showed that there was a difference in the test scores after the experimental group participants learned adjectives using the Flipped Classroom Approach as compared to the traditional teaching approach. The learners found it more effective to grasp knowledge during face-to-face lesson as they had acquired the relevant input online before the lesson. This study has provided insights for Malaysian primary ESL teachers to implement Flipped Classroom Approach in their classroom settings.